DIFFERENCE IN SERUM PSA LEVEL AND IIEF-5 BEFORE AND AFTER TURP IN BPH PATIENTS WITHOUT URINARY RETENTION - Hasibuan, Zulfian; Wirjopranoto, Soetojo; Djatisoesanto, Wahjoe; Pujiraharjo, Widodo J (Indonesian Journal of Urology, 2012)
Objective: Determine change in serum prostate-specific antigen (PSA) and International Index of Erectile Function (IIEF-5) following transurethral resection of the prostate (TURP). Material & Method: Eighteen men with age range of 50 – 69 years, were divided in two groups, group I 50-59 years (mean 56,5) and group II 60-69 years (mean 67,2). Both groups underwent measurement of serum PSA and IIEF-5 pre-operative, and repeated at 30, 60, and 90 days after TURP. Results: Level of serum PSA after TURP is decreased in most patients after 30, 60, and 90 days (72%, 72% and 78%). Mean value of PSA pre-operatively is 5,3 ± 3,3 ng/ml. After TURP, serum PSA level was 3,5 ± 3,0 ng/ml (30 days); 2,9 ± 2,9 ng/ml (60 days) and 1,8 ± 1,3ng/ml (90 days). Pre-operative PSA level was significantly decreased in Group I during the 60 and 90 days post TURP, while in Group II pre-operative PSA level was significantly decreased only in 90 days of observation. Overall there is no significant difference in PSA levels in both groups (p > 0,05). The decrease of PSA per gram resected in 30, 60, and 90 days were 0,10 ng/ml; 0,16 ng/ml and 0,24 ng/ml consecutively. There is no change in normal IIEF-5 score. Decrease of the IIEF-5 score in group I was measured at 30 days, but the score increased after 60 and 90 days. Meanwhile Group II showed decrease of IIEF-5 score. Pre-operative IIEF-5 score compared to the 30 days post TURP was significantly different but not significantly different compared with to score at 60 and 90 days. In Group I IIEF-5 score was significantly higher compared to Group II (p < 0,05). Prostatitis was found in 8 patients, but there is no difference in serum PSA level decrease between patients with or without prostatitis. Conclusion: There was significant decrease in serum PSA after TURP in BPH patients with LUTS at every measurement at 30, 60, and 90 days. PSA level after TURP depends on various factors, including pre-operative PSA, pre-operative prostate volume and prostate volume resected. Incidence of erectile dysfunction post TURP was low. Keywords: Prostate-specific antigen, benign prostatic hyperplasia, transurethral resection of the prostate, erectile dysfunction.